Evaluation of Canavalia ensiformis L. beans: Comparative Fatty Acid Profile in Extracts and Analysis of Minerals and Proximate Composition (International Journal of Biology and Chemistry, 2025)
This study investigates the proximate composition, mineral content, and fatty acid profile of Canavalia ensiformis L. beans extracted with various solvents. Proximate analysis revealed a high protein content (23.16%), moderate fiber levels (7.13%), and a total fat content of 2.35%. Elemental analysis identified potassium (18,696.87 mg/kg) as the most abundant macroelement, followed by calcium (1,886.81 mg/kg) and magnesium (1,500.98 mg/kg), whereas iron (50.43 mg/kg) and zinc (33.28 mg/kg) were the predominant microelements. Gas chromatography analysis of fatty acids showed that monounsaturated fatty acids (MUFA) dominated the lipid profile, particularly in the hexane (58.67%), ethanol (59.57%), and raw bean (61.11%) extracts. Oleic acid (C18:1n9c) was the most abundant MUFA, reaching 51.39% in the hexane extract. Saturated fatty acids (SFA) were highest in the hexane extract (21.35%), primarily due to palmitic acid (C16:0, 18.77%). Polyunsaturated fatty acids (PUFA) were most prevalent in the hexane extract (16.23%) and bean sample (16.08%), with linoleic acid (C18:2n6c) being the major component. The aqueous extract contained notable amounts of γ-linolenic acid (C18:3n6, 1.68%). These findings highlight the nutritional potential of C. ensiformis beans and suggest that solvent selection significantly influences lipid composition. The high MUFA and PUFA content, particularly in hexane and ethanol extracts, underscores their possible applications in food and pharmaceutical formulations.Key words: Canavalia ensiformis L., GC analysis, proximate analysis, micro- and macroelements, fatty acids.